"Ready-made" assumptions: Situating convenience as care in the Australian obesity debate. Issue 4 (2nd October 2019) - Warin, Megan; Jay, Bridget; Zivkovic, Tanya
Abstract: When it comes to food, eating and technologies, convenience is constructed as contradictory: on the one hand as a practice that saves time and effort, and on the other hand, an easy and often "unhealthy" choice, contributing to obesity rates. Moralizing, classed and gendered discourses around health and obesity mean that convenient options are rarely portrayed as "good choices". Through ethnographic research on food and families in the suburbs of an Australian city, this paper disrupts negative and polarized constructions of convenience in obesity debates. Building on the work of Mol et al. and Jackson et al. we argue that convenience is shaped by multiple contexts, and in particular, gendered and classed practices of care. In doing so, we suggest that public health interventions that construct convenience foods and technologies as wholly negative miss important cultural contexts in which convenience and care intersect to enhance social relationships.